Effect of Zinc, Iron and Manganese Levels on Quality, Micro and Macro Nutrients Content of Rice and Their Relationship with Yield. Issue 13 (20th July 2017) - Kumar, Ashok; Sen, Avijit; Upadhyay, Pravin Kumar; Singh, Ram Kumar
ABSTRACT: A field trial comprising three levels of zinc (Zn) 0, 5 and 10 kg ha-1, three levels of iron (Fe) 0, 15 and 30 kg ha-1 and three levels of manganese (Mn) 0, 5 and 10 kg ha-1 was carried out during the rainy seasons of 200 8 and 2009 at Varanasi, to study their effects on macro and micro nutrients content, yields and quality of rice variety HUBR 2–1. The experiment was conducted in 3 3 partial confounding with two replications. Half doses of all the micronutrients were applied as basal and the rest half through foliar application at different intervals. Among the treatments, Zn at 10 kg ha-1, iron at 15 kg ha-1 and Mn at 5 kg ha-1 recorded the maximum yield of rice. A similar trend was observed in all the quality parameters of rice. Individually Zn, Fe and Mn registered, respectively, 12.05, 8.60 and 4.46% more yield than the control.